2020
DOI: 10.1101/2020.10.02.20205831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A haemagglutination test for rapid detection of antibodies to SARS-CoV-2

Abstract: Serological detection of antibodies to SARS-CoV-2 is essential for establishing rates of seroconversion in populations, detection of seroconversion after vaccination, and for seeking evidence for a level of antibody that may be protective against COVID-19 disease. Several high-performance commercial tests have been described, but these require centralised laboratory facilities that are comparatively expensive, and therefore not available universally. Red cell agglutination tests have a long history in blood ty… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…Although the IgG antibodies to S1, S2 and the RBD rose from 4 to 12 weeks in the vaccinees, the ACE2 receptor blocking antibodies, which were shown to correlate with neutralizing antibodies significantly decreased 26 . The HAT assay, which also measures antibodies to the RBD and has shown to correlate well with the ACE2 receptor blocking assay and with neutralizing antibodies 23,27 , also showed that the RBD binding antibodies decreased from 4 to 12 weeks in the vaccinees. This suggests that although antibodies to RBD, S1 and S2 have increased in vaccinees from 4 to 12 weeks, they might not be neutralizing antibodies, possibly through targeting other epitopes in these regions.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although the IgG antibodies to S1, S2 and the RBD rose from 4 to 12 weeks in the vaccinees, the ACE2 receptor blocking antibodies, which were shown to correlate with neutralizing antibodies significantly decreased 26 . The HAT assay, which also measures antibodies to the RBD and has shown to correlate well with the ACE2 receptor blocking assay and with neutralizing antibodies 23,27 , also showed that the RBD binding antibodies decreased from 4 to 12 weeks in the vaccinees. This suggests that although antibodies to RBD, S1 and S2 have increased in vaccinees from 4 to 12 weeks, they might not be neutralizing antibodies, possibly through targeting other epitopes in these regions.…”
Section: Discussionmentioning
confidence: 87%
“…The HAT was carried out as previously described 23 . The B.1.1.7 (N501Y), B.1.351 (N501Y, E484K, K417N) and B.1.617.2 versions of the IH4-RBD reagent were produced as described 23 , but included the relevant amino acid changes introduced by site directed mutagenesis.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HAT was carried out as previously described using the B.1.1.7 (N501Y), B.1.351 (N501Y, E484K, K417N) and B.1.617.2 (L452R, T478K) versions of the IH4-RBD reagents 14 , which included the relevant amino acid changes introduced by site directed mutagenesis 15 . The assays were carried out and interpreted as previously described 16 .…”
Section: Haemagglutination Test (Hat) To Detect Antibodies To the Receptor Binding Domain (Rbd)mentioning
confidence: 99%
“…A titre of 1:20 was considered as a positive response, as previously determined by us 19 . The IH4-RBD reagents for each VOC were standardized by titration with the monoclonal antibody EY-6A 18,30 that binds to a conserved epitope common to all variants. A 20ug/ml solution of EY-6A titrated equally with a standard (2ug/ml) solution of each of the new IH4-RBD reagents.…”
Section: Haemagglutination Tests For Detection Of Antibodies To the Rbd In Wt And Sars-cov-2 Variantsmentioning
confidence: 99%